4y-3(y-4)+4=7

Simple and best practice solution for 4y-3(y-4)+4=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-3(y-4)+4=7 equation:


Simplifying
4y + -3(y + -4) + 4 = 7

Reorder the terms:
4y + -3(-4 + y) + 4 = 7
4y + (-4 * -3 + y * -3) + 4 = 7
4y + (12 + -3y) + 4 = 7

Reorder the terms:
12 + 4 + 4y + -3y = 7

Combine like terms: 12 + 4 = 16
16 + 4y + -3y = 7

Combine like terms: 4y + -3y = 1y
16 + 1y = 7

Solving
16 + 1y = 7

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 1y = 7 + -16

Combine like terms: 16 + -16 = 0
0 + 1y = 7 + -16
1y = 7 + -16

Combine like terms: 7 + -16 = -9
1y = -9

Divide each side by '1'.
y = -9

Simplifying
y = -9

See similar equations:

| -2(-x+y)=-2(-5) | | .5x+.5x=1x+1 | | 40-(3c+4)=5c+20 | | 5x-(2x+3)=6 | | 3/7-(1/2)^3 | | n/7+2=4 | | 41/5=15-(2t+3) | | 3w+9/5-9w+9/2=-30 | | 4x-27=-39+8x | | 1/2(-6+2p) | | 7/9+1/2(5/6)^2 | | (8x^2)/(8x^2+16x) | | -4b+5=2-8b-3b-11 | | 7z+1-5z=8+z-1 | | 4-5x=-8x+1 | | 2y+16+3y=-34 | | 34-5(x+1)=37 | | 8(2y-2)-(9y+5)= | | 9/7+1/2(5/6)^2 | | 8x^2/8x^2+16x | | 18x^2+9x-5= | | -x^2-11x+14=0 | | -7+13-6=-5a+6a | | X+2x+2=3x-13 | | -9=3m/4 | | x=49-4(2)(-8) | | 8r-18=-15+7r | | 9x=84+2x | | 5/6-1/36 | | 9w+1/7=5w-3/4+1 | | Y+(-14)=1 | | 0.4(2z+6)0.1=0.5(2z-3) |

Equations solver categories